An IoT Platform for Data Management in an Industrial-Scale Microalgae Cultivation Plant - M. Munoz; J. L. Guzman; M. Torres; F. G. Acien (IEEE Access, 2022)
Microalgae biomass production technology is in continuous progress. One of the challenges deals with scaling up existing medium-scale facilities to industrial-scale production systems. This new expanding infrastructure requires adequate data management and data accessibility tools for all the process variables. In this sense, this work presents a novel solution for microalgae production systems based on Internet of Things (IoT) technology as an important ally in the digitalization of these industrial processes. The paper summarizes the development of an IoT-based platform for data management in a large-scale microalgae cultivation plant with more than 12 industrial photobioreactors. A cloud-based architecture is provided for a solution for data management and a graphical front-end for data access (real-time and historical data). Different profiles can be managed for technicians and researchers depending on their skills and needs.